Volume 10: Heat Transfer, Fluid Flows, and Thermal Systems, Parts A, B, and C 2008
DOI: 10.1115/imece2008-66528
|View full text |Cite
|
Sign up to set email alerts
|

Showerhead Film Cooling Performance of a Turbine Vane at High Freestream Turbulence in a Transonic Cascade

Abstract: One way to increase cycle efficiency of a gas turbine engine is to operate at higher turbine inlet temperature (TIT). In most engines, the turbine inlet temperatures have increased to be well above the metallurgical limit of engine components. Film cooling of gas turbine components (blades and vanes) is a widely used technique that allows higher turbine inlet temperatures by maintaining material temperatures within acceptable limits. In this cooling method, air is extracted from the compressor and forced throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The negative and decreasing slopes at s/C > 0.15 are similar for low and medium BR. The case at BR = 4.0 exhibits the most rapid decrease in η av with increasing s/C, consistently with the results reported in [10]. When evaluating the influence of BR on the measured effectiveness around the leading edge (-0.2 < s/C < 0.35), the blowing condition at the medium BR resulted in the most effective cooling performance.…”
Section: Steady Predictions Vs Measurements Of Adiabatic Effectivenesssupporting
confidence: 87%
See 2 more Smart Citations
“…The negative and decreasing slopes at s/C > 0.15 are similar for low and medium BR. The case at BR = 4.0 exhibits the most rapid decrease in η av with increasing s/C, consistently with the results reported in [10]. When evaluating the influence of BR on the measured effectiveness around the leading edge (-0.2 < s/C < 0.35), the blowing condition at the medium BR resulted in the most effective cooling performance.…”
Section: Steady Predictions Vs Measurements Of Adiabatic Effectivenesssupporting
confidence: 87%
“…For a quantitative assessment of the impact of BR on film cooling effectiveness, η values were laterally averaged over the span section shown in Fig. 12 ( showing rapid decay within -0.2 < s/C < -0.05 is consistent with [10], where measurements were performed on a showerhead film cooled vane, with the same hole spanwise angle as that assumed here, at high mainstream turbulence.…”
Section: Steady Predictions Vs Measurements Of Adiabatic Effectivenessmentioning
confidence: 91%
See 1 more Smart Citation
“…Xue et al [24] demonstrated that compared to a showerhead only cooling case, the presence of an additional row of shaped holes can lead to a lower heat flux. The influence of exit Reynolds number/Mach number on the performance of showerhead cooling with respect to both film cooling effectiveness as well as Nusselt number has been investigated by Nasir et al [25]. In the presence of showerhead cooling, the AFE and overall cooling effectiveness of a cooling hole embedded in a trench on the pressure side is improved compared to the standard holes, as discussed by Albert and Bogard [26].…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…The paper discusses a new three-simulations technique to calculate vane surface recovery temperature, adiabatic wall temperature, and surface Nusselt number to completely characterize film cooling performance in a high speed flow. All of the 3D film cooling simulations are compared to the experimental data investigated by Nasir S. et al [11,12].…”
Section: Introductionmentioning
confidence: 99%